PHYSICAL AND PSYCHOSOCIAL EFFECTS OF HEART FAILURE IN PERCEIVED QUALITY OF LIFE - Mailson Marques de Sousa; Jacira dos Santos Oliveira; Maria Julia Guimarães Oliveira Soares; Simone Maria Muniz da Silva Bezerra; Simone Helena dos Santos Oliveira (Universidade Federal do Paraná, 2017)
The objective was to analyze the health-related quality of life of heart failure patients and to present an intervention proposal for the variables that most affect the perceived quality of life. Descriptive, cross-sectional study with a quantitative approach, involving 84 heart failure patients under outpatient follow-up, undertaken in the city of João Pessoa, PB, Brazil, between January and July 2015. The Minnesota Living Heart Failure Questionnaire was applied. The average total score on the Minnesota Living Heart Failure Questionnaire was 33.13±19.66, revealing a good quality of life. The physical aspects and difficulty to comply with the diet were the variables that most negatively influenced the perceived quality of life. Therapeutic strategies should be proposed with a multidisciplinary focus for the most affected physical and psychosocial aspects, with a view to minimizing the impact of the heart failure on the health-related quality of life.